Who behaves more pro-environmental in the national parks: A comparison of the tourist and the hiker. - Qing Zhang; Huazhen Sun; Xiasui Peng; Qiuyan Lin (PLoS ONE, 2023)
The intention of pro-environmental behavior (PEB) directly affects the sustainable development of protected areas, especially national parks, but few studies have done comparative research on tourist and hiker behaviors. This study explores the intention of tourists' and hikers' pro-environmental behavior based on theory of planned behavior (TPB) and norm activation theory (NAM). Researchers surveyed 454 tourists and 466 hikers in Wuyishan National Park a structural equation modeling data analysis method. The results demonstrate that the TPB and the NAM were accurate in describing for tourists' and hikers' pro-environmental behavior in national park. However, for specific influencing factors, hikers' attitude, awareness of consequences, and assumption of responsibility were significantly different from those of the tourists. This study sheds light on how to better comprehend and advocate for PEB in national parks and proposes different management approaches to improve the PEB of tourists and hikers.